Penerapan Model Guided Discovery Learning Untuk Meningkatkan Pemahaman Konsep Matematis Mahasiswa - Muhammad, Guntur Maulana; Karso, Karso (Fakultas Matematika dan Ilmu Pengetahuan Alam, 2018)
This action research is based on the implementation Guided Discovery Learning (GDL) in the 2013 curriculum (K13) for education in Indonesia. Beside that the minimum completeness criteria, for space analytic geometry in Suryakancana University, has not been achieved yet. The aim of this study was to improve the mathematical conceptual understanding of students who were taking lectures on space analytic geometry. The sample consisted of two classes with many students of 19 and 22 respectively. This classroom action research was completed in two cycles. In the second cycle, the class absorption of each class was 78.95% and 77.27%. Thus it can be concluded that the implementation of the GDL model can improve the ability to understand students mathematical concepts, especially in the analytic geometry of space subject, and in general students provide a positive response to learning with the GDL model.